Seas of trouble: Enduring territorial conflicts in East and Southeast Asia - Felix Heiduk; Michael Paul (Stiftung Wissenschaft und Politik (SWP), 2015)
In the last five years, tensions have increased between China and a number of neighboring states over territorial disputes in the East and South China Sea. In some cases, there have even been threats of armed conflicts. China's increasingly aggressive behavior has stoked fears that long-simmering conflicts could escalate. This dismal picture began to brighten considerably, however, in the last half of 2014. In November, in the run-up to several important international summit meetings in the region, including the ASEAN Summit and the East Asia Summit (EAS), the parties to the conflicts began cautiously moving closer to one another and the security situation improved. Nevertheless, the drivers of the conflicts remain unchanged. They include conflicting territorial claims, strategic misperceptions, and contested regional orders. (SWP Comments)
Keywords: 320